The theory of sustainability from Islamic perspective - Abdul Latiff, Zainab; Mohd Yunus, Mohd Yazid; Othuman Mydin, Md Azree (American - Eurasian Network for Scientific Information, A E N S I Publications, 2016)
The term sustainability has been widely used in all walks of life. The common definition put by Brutland Commision 1987 of ‘meeting needs of the present without comprising th e ability of future generations to meet their own needs' has faced numerous criticism when resources are given the most attention while neglecting the fact that it is being manipulated, depleted and destroyed. Therefore, this paper presents Islamic views on sustainability by adopting the method of content analysis of cross reference by focusing mostly on the work of Ibn Taymiyyah and Said Nursi in extracting the theories and principles of sustainability as a whole and in a multi-religious society specifically. The principles that define a sustainable environment has also been established. This paper concludes that man who has been entrusted to make the universe the best place to live must adhere to four fundamental principles 1] daily purification of the soul [tazkiyatun nafs], 2] supplication of God’s dominicality [rububiyyah], 3] vicegerent [khalifah] and 4] vicegerent on Earth[khalifatu fil ardh].